Avaliação da influência do background genético murino na inflamação, angiogênese e fibrogênese intraperitoneal induzidas por implantes - Suzane Mota Marques Costa (2016)
Genetic differences between individuals of the same species have been associated with distinct morphological and functional features in a large number of pathophysiological processes. We characterized the acute inflammatory response and chronic adhesion formation and the effect of dipyridamole using a synthetic matrix deployment model in the peritoneal cavity four strains of mice: DBA / 1, Swiss, C57BL / 6 and Balb / c . In vascular permeability, as assessed by fluorescein diffusion technique, it was observed that the animals had different responses, with Balb / c and C57BL / 6 showing lower permeability marker. There were also marked differences in the release / levels of most of the assessed inflammatory markers in the intraperitoneal washed between the lines, both at baseline and in response to the implant. Basal lavage of animals showed that the animals Swiss strains showed higher levels of the enzyme Nacetyl-β-D-glucosaminidase (NAG) and of the chemokine CCL-2. However, after implantation, the washing of animals BALB / c had higher MPO levels, CCL-2 when compared to other strains. For evaluation of chronic inflammation, angiogenesis and fibrogenesis tissues induced by the synthetic matrix implant in the peritoneal cavity were characterized. Angiogenesis, the content evaluated intra-implant hemoglobin was higher in Swiss mice, whereas the levels of the growth factor vascular endothelium (VEGF) were higher in C57BL / 6 mice. The levels of proinflammatory cytokines and enzymes (MPO and NAG) were also strain dependent. The pro-fibrogenic markers transforming growth factor (TGFβ1) and collagen under way in mice DBA / 1, while in animals C57BL strains / 6 showed elevated levels. differential sensitivity to dipyridamole was also observed, with pro-angiogenic effects in animal implants DBA / 1 but antiangiogenic effects in Swiss animal implants. These important differences related to strain in the development of peritoneal fibrosis and in response to dipyridamole should be considered in the design and analysis of studies on fibrogenesis in mice.